2004
DOI: 10.1088/0953-8984/16/43/016
|View full text |Cite
|
Sign up to set email alerts
|

A single-crystal high-pressure x-ray diffraction study of decagonal Al–Co–Cu up to 19.1 GPa

Abstract: An in situ single-crystal high-pressure x-ray diffraction study of decagonal Al–Co–Cu up to 19.1 GPa has been performed using diamond anvil cells and synchrotron radiation. Quantitative reciprocal space reconstruction from image plate data was used for data analysis. No significant variations with pressure were observed in Bragg as well as diffuse scattering, indicating the high stability of the quasiperiodic structure in the investigated pressure range. The bulk modulus at zero pressure was determined from fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In a feasibility study it was shown that it is possible to obtain diffraction images with a comparable amount of information with and without DAC [1]. The change of the design of the DAC, in this case the replacement of polycrystalline Be by single-crystalline diamond further improved the obtainable quality of the data [2,3]. Mg 2 Co 3 Sn 10þx [4] was chosen for the present single-crystal hp study and bonding analysis, because of the following reasons:…”
Section: Introductionmentioning
confidence: 99%
“…In a feasibility study it was shown that it is possible to obtain diffraction images with a comparable amount of information with and without DAC [1]. The change of the design of the DAC, in this case the replacement of polycrystalline Be by single-crystalline diamond further improved the obtainable quality of the data [2,3]. Mg 2 Co 3 Sn 10þx [4] was chosen for the present single-crystal hp study and bonding analysis, because of the following reasons:…”
Section: Introductionmentioning
confidence: 99%
“…Therefore single-crystal investigations at high pressures and high temperatures are of special interest. It has been shown recently that diffraction patterns from single crystals of decagonal quasicrystals obtained at ambient temperature using a diamond-anvil cell (DAC) and reciprocal-space imaging techniques yield a comparable number of observable diffraction features as measurements without a DAC [5,6]. A recent high-pressure study on single-crystalline icosahedral Al-Pd-Mn has demonstrated that it is possible to determine the bulk modulus of a quasicrystal with comparable accuracy to periodic crystals [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recent high-pressure studies on decagonal AlCoCu to 20 GPa and AlCoNi to 10 GPa demonstrate the improved quality of diffraction data when experiments are carried out on single-grain using angle-dispersive x-ray diffraction technique [20]. It was concluded that neither Bragg scattering nor diffuse scattering are volume dependent in decagonal alloys in the pressure range investigated.…”
mentioning
confidence: 98%